Progressive legal perspective on legal certainty over land ownership in Genteng Village - Ramadani, Jaka Mahisya; Firdaus, Wildan Abyan; Milyanti, Mia; Maulida, Irma; Andri, Gusti Yosi (Indonesian Journal of Multidisciplinary Science, 2024)
Land ownership affects power structures and power relations in societies because it determines who has access to natural resources and available economic wealth. Land ownership is also a determinant of a person's social and political status, as well as the basis for access to public services such as education and health. This study aims to explore the perspective of progressive law on legal certainty of land ownership in Genteng Village as well as the view of behavioral economic theory to understand the habits of the people of Genteng Village in buying and selling land. The research method used is empirical juridical with a case study approach in the form of land buying and selling habits in Genteng Village without positive legal formalities. Data were collected through structured interviews with local stakeholders related to the problem studied. The results of the study show that the practice of land ownership in Genteng Village is often based on proof of sale and purchase such as sales and purchase receipts, without a positive legal process such as adequate certification or name change. The behavioral economic theory sees that the habits of the people of Genteng Village are only temporary and inconsistent in nature so that they can change in the future. The perspective of progressive law that emphasizes more on the aspect of justice views that the existing legal certainty must contain formal aspects and substantial aspects.